Evaluation of the environmental quality in classrooms: A Systematic Review - Canelada, Andre; Fontes, Maria Solange Gurgel de Castro; Magagnin, Renata Cardoso; Azambuja, Maximiliano dos Anjos (Technical and Scientific Journal Green Cities, 2024)
Ensuring environmental quality, such as thermal, acoustic or visual, in classrooms is an essential factor for high productivity among those who use this space, because these are places where users spend most of the day. Measuring these parameters in these environments can be done using different qualitative and quantitative methodologies, being the most common the on-site measurements of temperature, luminance and noise, along with the application of questionnaires to understand the perceptions of those who use the location. In this context, the article aimed to identify the most common methods for measuring the environmental quality of classrooms in the specific literature. To this end, a systematic literature review was carried out using the ScienceDirect and Scopus databases, based on the selection of 29 articles, which made up the sample size. With the individual analysis the articles, the importance of carrying out post-occupancy evaluation experiments in school spaces is highlighted, taking into account personal variables between human beings, as well as different microclimatic and cultural contexts, as users’ perception of the built environment may be interfered according to these criteria. The analysis of the bibliography provides a general overview of the researches developed around the world, being able to serve as a basis for work related to the topic. Furthermore, the references indicated a gap regarding the lack of articles that use methodologies other than conventional ones, mainly in relation to qualitative methodologies for evaluating a physical space of the classrooms.